The Influence of Work Environment and Workload on Employees’ Turnover Intention at PT Mayora Indah Tbk - Wijaya, Tedi Surya (CNPLUS Publisher, 2025)
This study investigates the impact of work environment and workload on employees' turnover intention at PT Mayora Indah Tbk. Using a quantitative approach, data were gathered through questionnaires distributed to 60 employees selected via purposive sampling. The analysis employed multiple linear regression using SPSS software. The findings indicate that the work environment has a significant positive effect on turnover intention, while workload has a significant negative effect. Jointly, both variables significantly influence turnover intention, with a coefficient of determination (R²) of 64.8%, suggesting a strong contribution to employees’ intention to leave. The research is limited by its focus on a single company and a relatively small sample, affecting generalizability. Nonetheless, the study offers practical insights for improving employee retention through better work environments and manageable workloads. It also highlights the broader social importance of reducing turnover to enhance job stability and employee well-being. This research contributes valuable empirical evidence on the dual influence of organizational factors on turnover intention within the Indonesian FMCG sector.